Tsentsak: la experiencia chamánica en el pueblo Shuar - Antun' Tsamaraint', Raquel Y.; Chiriap Inchit, Víctor H. (Abya-Yala, 1991)
"Produced by the Shuar of Ecuador, work focuses on shamanism and shamanic forces (tsentsak, darts). Includes biographies and interviews with Shuar shamans, and discussions of the shamans' practice, classes of shamans, initiation and trance experiences, and witchcraft. Particularly valuable insider perspective, with reflections on anthropological interpretations of Shuar shamanism"--Handbook of Latin American Studies, v. 57